G6PD Deficiency Prevalence as a Cause of Neonatal Jaundice in a Neonatal Ward in Dohuk, Iraq - Eissa, Adil Abozaid; Haji, Bijar Ali; Al-Doski, Adnan Anwar (American Journal of Perinatology, 2019)
Objective The current study initiated to address the effect of glucose-6-phosphate dehydrogenase (G6PD) deficiency on the pathogenesis and the severity of neonatal hyperbilirubinemia (NHB).Study Design A total of 100 newborns with moderate to severe indirect hyperbilirubinemia and 50 normal neonates without hyperbilirubinemia had been enrolled in the current case–control study. All enrolled neonates had been tested for ABO and Rh(D) blood grouping, Total serum bilirubin measurement, complete blood count, morphology, reticulocyte counts, direct Coombs' test, and G6PD enzyme assay.Results From all enrolled hyperbilirubinemic neonates, 16% were G6PD deficient and this displays a statistically significant difference in comparison to controls (only 6% were G6PD deficient). Also, significant difference was found in the level of serum indirect bilirubin among G6PD-deficient neonate in comparison to G6PD nondeficient neonates which had contributed significantly to the difference in the duration of phototherapy and hospitalization among deficient neonate. Despite this, no significant difference found in the onset of presentation, reticulocytes count, and age of neonates between the two groups (G6PD-deficient and G6PD nondeficient neonates).Conclusion The current study augments the etiological role of G6PD in the causation and severity of NHB in the region; however, in the absence of significant difference in the reticulocytes and the hemoglobin level, the underlying mechanism cannot be backed to the excess hemolysis alone.
Keywords: G6PD deficiency; neonatal hyperbilirubinemia; phototherapy; exchange transfusion